Status of birth preparedness and complication readiness in Uttar Dinajpur District, West Bengal - Dipta Kanti Mukhopadhyay; Sujishnu Mukhopadhyay; Sharmistha Bhattacharjee; Susmita Nayak; Asit K Biswas; Akhil B Biswas (Wolters Kluwer Medknow Publications, 2013)
Context: Birth Preparedness and Complication Readiness (BPCR) is crucial in averting maternal morbidity and mortality. Objectives: To find out awareness and practices regarding BPCR among pregnant and recently delivered women in Uttar Dinajpur, West Bengal. Materials and Methods: This is a cross-sectional, community-based, mixed methods study. Two-stage, 40 cluster sampling technique was used to select three pregnant and six recently delivered women separately. Information on socio-demographic variables as well as awareness and practices regarding BPCR were collected through semi-structured interview. In-depth interviews with one respondent per cluster were also conducted. For statistical analysis Z test was used. Results: Around 50% of the respondents planned for first antenatal check-up (ANC) within 12 weeks, four or more ANCs and institutional delivery. Proportion of women aware of at least one key danger sign each of pregnancy, labor, postpartum, and newborn ranged from 12.1% to 37.2%, whereas 58.3% knew at least one key component of essential newborn care. Around two-thirds and one-third of women, respectively, especially those from backward and below poverty line (BPL) families knew about cash incentive and referral transport schemes. Proportions of women with first ANC within 12 weeks, four or more ANCs, institutional delivery, saving money, identifying transport, and blood donor were 50.4%, 33.6%, 46.2%, 40.8%, 27.3%, and 9.6%, respectively. Hindu religion, backward castes, BPL status, and education ≥ 5 years influenced the practices except for two regarding ANC. Overall BPCR index of the study population was 34.5. Conclusion: Preparedness in health system, ensuring competence, and motivation of workers are needed for promoting BPCR among the study population.